Peptides from the plasmodium falciparum STEVOR putative protein bind with high affinity to normal human red blood cells (2005)
Synthetic 20-mer long non-overlapped peptides, from STEVOR protein, were tested in RBC binding assays for identifying STEVOR protein regions having high RBC binding activity and evaluating whether these regions inhibit Plasmodium falciparum in vitro invasion. Affinity constants, binding site number per cell and Hill coefficients were determined by saturation assay with high activity binding peptides (HABPs). HABP binding assays using RBCs previously treated with enzymes were carried out to study the nature of the receptor. The molecular weight of RBC surface proteins interacting with HABPs was determined by cross-linking assays and SDS-PAGE analysis. RBC binding assays revealed that peptides 30561 (41MKSRRLAEIQLPKCPHYNND60), 30562 (61PELKKIIDKLNEERIKKYIE80) and 30567 (161ASCCKVHDNYLDNLKKGCFG180) bound saturably and with high binding activity, presenting nanomolar affinity constants. HABP binding activity to RBCs previously treated with neuraminidase and trypsin decreased, suggesting that these peptides bound to RBC surface proteins and that such binding could be sialic acid dependent. Cross-linking and SDS-PAGE assays showed that the three HABPs specifically bound to 30 and 40 kDa molecular weight RBC membrane proteins. Peptides 30561, 30562 and 30567 inhibited P. falciparum in vitro invasion of red blood cells in a concentration-dependent way. Goat sera having STEVOR protein polymeric peptides antibodies inhibit parasite in vitro invasion depending on concentration. Three peptides localized in STEVOR N-terminal and central regions had high, saturable, binding activity to 30 and 40 kDa RBC membrane proteins. These peptides inhibited the parasite's in vitro invasion, suggesting that STEVOR protein regions are involved in P. falciparum invasion processes during intra-erythrocyte stage.